Partnership of I-ACT for children (US) and European pediatric clinical trial networks to facilitate pediatric clinical trials - Degraeuwe, Eva; Hovinga, Collin; De Maré, Annelies; Fernandes, Ricardo M.; Heaton, Callie; Nuytinck, Lieve; Persijn, Laura; Raes, Ann; Vande Walle, Johan; Turner, Mark A. (Frontiers in Pediatrics, 2024)
Case study of a transatlantic partnership between two pediatric clinical trial facilitation networks for both rare and general indications across High Income Countries. Metrics of clinical trial facilitation to improve drug labelling and adequate use in children. Findings showcase shortcoming and improving quality of trial country and site selection. We make the case that for the upcoming increase in pediatric clinical trials, the use of facilitation networks has a considerable positive impact on start-up timelines and success ratio of a pediatric clinical trial.